Yttrium-zirconium composite nano-ceramic powder and its preparation method and application

Through specific raw materials and preparation methods, yttrium zirconium composite nanoceramic powder is prepared, which solves the problems of insufficient thermal expansion coefficient and powder agglomeration of yttrium zirconium ceramic materials, and achieves higher density and thermal expansion performance. It is suitable for the preparation of aerospace and heat-resistant ceramic materials.

CN119330708BActive Publication Date: 2025-04-18SHANDONG MENGXI NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411460218.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-04-18
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The thermal expansion coefficient of existing yttrium zirconium ceramic materials is insufficient, which leads to easy shedding when used in aerospace and refractory materials. At the same time, the agglomeration of nano powders and the presence of pores also affects densification.

Method used

Through specific raw materials and preparation methods, yttrium zirconium composite nanoceramic powder is prepared, including mixing ZrOCl2·8H2O with Y2O3 solution, then mixing with nanosilicon dioxide, MgO, B2O3 and other substances and quenching and water quenching. Finally, KAlSiO4, water glass and phosphate are added for grinding to form a uniformly distributed yttrium zirconium composite ceramic powder.

Benefits of technology

The uniform particle size distribution of yttrium zirconium composite ceramic powder is achieved, the firing temperature is reduced, the grain growth is suppressed, the density and thermal expansion performance are improved, and it is suitable for the preparation of aerospace and heat-resistant ceramic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091655430000111
    Figure BDA0005091655430000111
Patent Text Reader

Abstract

The present invention relates to the technical field of ceramic materials, and specifically to a yttrium-zirconium composite nano-ceramic powder and a preparation method and application thereof, comprising the following steps: ZrOCl 2 8H 2 O was dissolved in water and (NH 4 ) 2 SO 4 , heat until solid precipitates, cool and filter to obtain Zr(SO 4 ) 2 ; Y 2 O 3 Dissolve in hydrochloric acid solution to obtain YCl 3 Solution; Zr(SO 4 ) 2 Dissolve in water and mix with YCl 3 The solution was mixed, an alkaline solution was added dropwise and the pH was controlled to be 10-13, a surfactant was added, filtered and washed to obtain a yttrium-zirconium composite precipitate; and nano-silicon dioxide, MgO, B 2 O 3 Mix, smelt for 2-5 hours, pour into polyethylene glycol solution for water quenching, filter to obtain yttrium-zirconium composite ceramic fragments; add KAlSiO 4 , water glass and phosphate, grind and dry to obtain yttrium zirconium composite nano ceramic powder. The present application makes the nano powder less likely to agglomerate and the particle size distribution more uniform by matching specific raw materials and preparation methods, while improving the thermal expansion coefficient of yttrium zirconium composite ceramics, which is convenient for preparing aerospace and heat-resistant ceramic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic materials, and in particular to an yttrium-zirconium composite nano-ceramic powder and a preparation method and application thereof. Background Art

[0002] Nanoceramics is a composite material made by introducing nano-scale ceramic particles, whiskers, fibers, etc. into a ceramic matrix, or by sintering nano-ceramic powder. It significantly improves the shortcomings of traditional ceramics such as high brittleness and poor processing performance, improves the room temperature mechanical properties of the matrix material, and improves high temperature performance.

[0003] Zirconia ceramic material has good wear resistance and corrosion resistance, and is an inorganic non-metallic material with excellent physical and chemical properties. It is not only used in structural ceramic devices such as cutting tools and abrasives due to its good mechanical properties, but also in functional ceramic fields such as ceramic capacitors and fuel cells.

[0004] However, in aerospace and some refractory materials, the thermal expansion coefficient of materials is required to be higher. Usually, the thermal expansion coefficient of yttrium zirconium ceramics can reach 10.3×10 -6 / ℃, although higher than alumina ceramics, it still cannot fully meet the needs. For example, the thermal expansion coefficient of stainless steel can reach 18×10 -6 / ℃, when yttrium zirconium ceramics are coated on the surface of stainless steel, the difference in thermal expansion coefficients easily causes the yttrium zirconium ceramic coating to fall off. In addition, when yttrium zirconium ceramic powder reaches the nanoscale, the specific surface area increases sharply, and the surface effect causes the powder to spontaneously agglomerate. Due to the agglomeration of the powder, individual grains will grow abnormally, and eventually pores will exist in the ceramic body, making it impossible to achieve densification. Summary of the invention

[0005] The present application aims to overcome at least one of the defects of the prior art and provide a yttrium-zirconium composite nano-ceramic powder and its preparation method and application. By matching specific raw materials and preparation methods, the nano-powder is not easy to agglomerate and the particle size distribution is more uniform. At the same time, the thermal expansion coefficient of the yttrium-zirconium composite ceramic is improved, which is convenient for the preparation of aerospace and heat-resistant ceramic materials.

[0006] In the first aspect, the present application provides a method for preparing yttrium-zirconium composite nano-ceramic powder, which is achieved by the following technical solutions:

[0007] A method for preparing yttrium-zirconium composite nano-ceramic powder comprises the following steps:

[0008] (1) dissolving ZrOCl2·8H2O in water, adding (NH4)2SO4, heating until solid precipitates, cooling, filtering to obtain Zr(SO4)2; dissolving Y2O3 in a hydrochloric acid solution to obtain a YCl3 solution; dissolving the Zr(SO4)2 in water, then mixing with the YCl3 solution, dropping an alkaline solution and controlling the final pH of the system to be 10-13, adding a surfactant, filtering, washing, and obtaining a yttrium-zirconium composite precipitate;

[0009] (2) mixing the yttrium-zirconium composite precipitate described in step (1) with nano-silicon dioxide, MgO, and B2O3, smelting for 2-5 hours, pouring into a polyethylene glycol solution for water quenching, and filtering to obtain yttrium-zirconium composite ceramic fragments;

[0010] (3) adding KAlSiO4, water glass and phosphate to the yttrium-zirconium composite ceramic fragments of step (2), grinding and drying to obtain yttrium-zirconium composite nano-ceramic powder;

[0011] Wherein, the weight ratio of Zr(SO4)2, Y2O3, alkaline solution and surfactant in step (1) is (70-85):(10-30):(5-15):(0.5-2);

[0012] The weight ratio of the yttrium-zirconium composite precipitate, nano-silicon dioxide, MgO and B2O3 in step (2) is (60-80):(30-40):(1-2):(8-12);

[0013] The weight ratio of the yttrium-zirconium composite ceramic fragments, KAlSiO4, water glass and phosphate in step (3) is (60-70):(30-40):(10-20):(1-3).

[0014] According to the method for preparing yttrium-zirconium composite nano-ceramic powder according to the embodiment of the present application, there are at least the following beneficial effects:

[0015] In the present application, yttrium zirconium composite precipitate is mixed with nano-silicon dioxide, MgO, and B2O3 for melting and water quenching. Nano-silicon dioxide, B2O3, and MgO can form a glass phase, so that the mass transfer mechanism is changed from solid-phase diffusion to liquid-phase flow, which promotes mass transfer, helps to reduce the firing temperature, inhibits grain growth, and improves density. By fusing the yttrium zirconium composite ceramic phase with the glass phase, the components are mixed more fully, the sintering temperature can be reduced, and the thermal expansion properties of the yttrium zirconium composite ceramic can be enhanced.

[0016] The addition of surfactant, polyethylene glycol solution and phosphate in the preparation method of the present application can improve the surface activity of yttrium zirconium nanopowder, reduce the agglomeration of powder, and make the particle size distribution more uniform. The hydroxyl and ether oxygen groups in the polyethylene glycol molecule can form strong hydrogen bonds with the surface of the precipitated particles, and its oxygen ether group is also easy to have affinity with the surface of the precipitated particles. This interaction allows polyethylene glycol to be easily adsorbed on the surface of the particles to form a layer of polymer film, surrounding the precipitated particles, thereby effectively preventing the agglomeration of particles. Therefore, polyethylene glycol can form colloidal particles in aqueous solution and effectively prevent the aggregation of particles through steric hindrance effect, thereby maintaining the stability of the dispersed system; phosphate can be adsorbed on the surface of powder particles, change its surface characteristics, reduce the attraction between particles, thereby preventing the agglomeration and agglomeration between particles, and can also maintain the dispersed state of particles, thereby improving the stabilization effect on yttrium zirconium composite nano-ceramic powder.

[0017] The KAlSiO4 of the present application is a complex crystal composed of polyhedral coordination and has high thermal expansion. By being matched with yttrium-zirconium composite ceramics, the thermal expansion coefficient of yttrium-zirconium composite ceramics can be improved.

[0018] The MgO in the present application is dissolved in ZrO2, which increases the ion defect concentration that controls the diffusion process, thereby promoting sintering densification; at the same time, the addition of MgO can increase the mobility of the pores, allowing the pores to escape before the grains grow, which is beneficial to the densification of the yttrium-zirconium composite ceramic.

[0019] The water glass of the present application is used as an adhesive, and forms a silicon-oxygen network through self-polymerization by water evaporation, so as to effectively bond the yttrium-zirconium composite ceramic powder together, thereby generating higher strength. Meanwhile, the water glass and stainless steel have good wettability, and can be spread on the surface of the stainless steel, so as to tightly bond the stainless steel and the coating material together. After high-temperature heat treatment, a glass phase and sodium disilicate crystals are formed. The glass phase can infiltrate the surface of each yttrium-zirconium composite ceramic powder particle and form a glass phase bonding layer between the particles. Meanwhile, the glass phase can dissolve the oxide layer on the surface of the stainless steel to form a transition layer containing a high amount of iron ions, thereby ensuring the continuity of the interface in terms of electronic structure and atomic structure, so that the yttrium-zirconium composite nano-ceramic forms a complex chemical bond with the stainless steel surface, thereby further improving the adhesion strength of the yttrium-zirconium composite nano-ceramic coating. The sodium disilicate crystals appear in the shape of needles, interspersed between each yttrium-zirconium composite ceramic powder particle, and play a role in short fiber reinforcement.

[0020] According to some embodiments of the present application, the surfactant in step (1) is selected from one of ethanol, isopropanol, glycerol, and citric acid.

[0021] According to some embodiments of the present application, the alkaline solution in step (1) is selected from one of aqueous ammonia, ammonium carbonate, caustic soda, and urea.

[0022] According to some embodiments of the present application, the average particle size of the nano-silicon dioxide in step (2) is 15 nm. Nano-silicon dioxide of this particle size helps to lower the smelting temperature, reduce energy consumption, improve the fluidity of the melt, make the smelting process smoother, and reduce smelting time and cost.

[0023] According to some embodiments of the present application, the smelting in step (2) is heated by intermittent heating. Intermittent heating allows the time and interval of heating to be controlled during the smelting process, so that the material has an appropriate cooling time in the molten state, thereby avoiding quality instability caused by overheating. Through intermittent heating, it can be ensured that the material has sufficient time to diffuse and mix during the smelting process, making the composition more uniform and improving the overall quality of the composite ceramic.

[0024] Furthermore, the intermittent heating is stopped for 10 minutes every 20-30 minutes.

[0025] Furthermore, the heating temperatures during the intermittent heating are 1800° C., 1200° C., and 600° C., respectively, and the heating is cycled sequentially after each interval.

[0026] According to some embodiments of the present application, the grinding in step (3) is wet ball milling.

[0027] Furthermore, the rotation speed of the wet ball mill is 300-600 r / min; further 300-550 r / min.

[0028] Furthermore, the wet ball milling time is 10-40 hours; furthermore, 12-36 hours.

[0029] According to some embodiments of the present application, the grinding in step (3) is followed by sieving, and further, the sieving is used to control the particle size distribution range of the product to be 50-200 nm. This particle size can better balance the sinterability of the yttrium-zirconium composite nano-ceramic material and the fluidity of the powder, and is more conducive to improving the mechanical properties of the ceramic material.

[0030] According to some embodiments of the present application, other additives may be added before grinding in step (3).

[0031] Furthermore, the other additives include at least one of BaO, K2O, Na2O, CaO, and Li2O. Adding an appropriate amount of additives can effectively inhibit the anisotropic growth of grains, which is conducive to the uniform distribution of ZrO2 grain size, and Ba 2+ , K + 、Na + , Ca 2 + , Li + With Y3+ 、Zr 4+ The radius and electricity price of Zr 4+ The lattice is activated, which reduces the sintering activation energy, thereby reducing the sintering temperature and increasing the density of the yttrium-zirconium composite nanoceramics.

[0032] In a second aspect, an embodiment of the present application provides yttrium-zirconium composite nano-ceramic powder produced by the above-mentioned method for preparing yttrium-zirconium composite nano-ceramic powder.

[0033] The yttrium-zirconium composite nano-ceramic powder according to the embodiment of the present application has at least the following beneficial effects:

[0034] The yttrium-zirconium composite nano-ceramic powder of the present application is not easy to agglomerate, and the particles are evenly distributed, which can improve the density and thermal expansion performance of the yttrium-zirconium composite ceramic material.

[0035] In a third aspect, the embodiments of the present application provide the application of the above-mentioned yttrium-zirconium composite nano-ceramic powder in the production of heat-resistant ceramics and aerospace.

[0036] In the fourth aspect, an embodiment of the present application provides an application of the above-mentioned yttrium-zirconium composite nano-ceramic powder in the production of a ceramic coating on the surface of stainless steel; the prepared yttrium-zirconium composite nano-ceramic has a thermal expansion coefficient close to that of stainless steel, is firmly bonded, and is not easy to fall off, which not only enhances the wear resistance of stainless steel, but also improves the mechanical properties of the ceramic. DETAILED DESCRIPTION

[0037] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.

[0038] Example 1

[0039] Preparation of Yttrium-Zirconium Composite Nano-Ceramic Powder:

[0040] (1) dissolving ZrOCl2·8H2O in water, adding (NH4)2SO4, heating until solid precipitates, cooling, filtering, and obtaining Zr(SO4)2; dissolving Y2O3 in a hydrochloric acid solution to obtain a YCl3 solution; dissolving the Zr(SO4)2 in water, then mixing it with the YCl3 solution, dropping an ammonia solution and controlling the final pH value of the system to be 10-13, adding glycerol, filtering, and washing to obtain a yttrium-zirconium composite precipitate; wherein the weight ratio of the Zr(SO4)2, Y2O3, alkaline solution, and surfactant is 78:20:10:1;

[0041] (2) mixing the yttrium zirconium composite precipitate described in step (1) with nano-silicon dioxide, MgO and B2O3, smelting for 4 hours, pouring into a polyethylene glycol solution for water quenching, and filtering to obtain yttrium zirconium composite ceramic fragments; wherein the weight ratio of the yttrium zirconium composite precipitate, nano-silicon dioxide, MgO and B2O3 is 70:35:1.5:10, and the smelting is heated by intermittent heating, and the intermittent heating is stopped for 10 minutes after every 25 minutes of heating. The heating temperatures during the intermittent heating are 1800° C., 1200° C. and 600° C., respectively, and the process is repeated in sequence after each pause. The average particle size of the nano-silicon dioxide is 15 nm;

[0042] (3) Adding KAlSiO4, water glass, phosphate and BaO to the yttrium-zirconium composite ceramic fragments of step (2), wet-milling at a rotation speed of 450 r / min for 25 h, drying and sieving to obtain yttrium-zirconium composite nano-ceramic powder; wherein the weight ratio of the yttrium-zirconium composite ceramic fragments, KAlSiO4, water glass, phosphate and BaO is 65:35:15:2:1.

[0043] Example 2

[0044] Preparation of Yttrium-Zirconium Composite Nano-Ceramic Powder:

[0045] (1) dissolving ZrOCl2·8H2O in water, adding (NH4)2SO4, heating until solid precipitates, cooling, filtering to obtain Zr(SO4)2; dissolving Y2O3 in a hydrochloric acid solution to obtain a YCl3 solution; dissolving the Zr(SO4)2 in water, then mixing it with the YCl3 solution, adding a sodium carbonate solution dropwise and controlling the final pH value of the system to be 10-13, adding ethanol, filtering, washing, and obtaining a yttrium-zirconium composite precipitate; wherein the weight ratio of the Zr(SO4)2, Y2O3, alkaline solution, and surfactant is 85:10:15:0.5;

[0046] (2) mixing the yttrium zirconium composite precipitate described in step (1) with nano-silicon dioxide, MgO and B2O3, smelting for 2 hours, pouring into a polyethylene glycol solution for water quenching, and filtering to obtain yttrium zirconium composite ceramic fragments; wherein the weight ratio of the yttrium zirconium composite precipitate, nano-silicon dioxide, MgO and B2O3 is 80:30:2:8, and the smelting is heated by intermittent heating, and the intermittent heating is stopped for 10 minutes after every 30 minutes of heating. The heating temperatures during the intermittent heating are 1800° C., 1200° C. and 600° C., respectively, and the process is repeated in sequence after each pause. The average particle size of the nano-silicon dioxide is 15 nm;

[0047] (3) Add KAlSiO4, water glass, phosphate, Na2O and CaO to the yttrium-zirconium composite ceramic fragments of step (2), wet-mill at a speed of 300 r / min for 40 h, dry and sieve to obtain yttrium-zirconium composite nano-ceramic powder; wherein the weight ratio of the yttrium-zirconium composite ceramic fragments, KAlSiO4, water glass, phosphate, Na2O and CaO is 70:30:20:1:0.5:0.5.

[0048] Example 3

[0049] Preparation of Yttrium-Zirconium Composite Nano-Ceramic Powder:

[0050] (1) dissolving ZrOCl2·8H2O in water, adding (NH4)2SO4, heating until solid precipitates, cooling, filtering to obtain Zr(SO4)2; dissolving Y2O3 in a hydrochloric acid solution to obtain a YCl3 solution; dissolving the Zr(SO4)2 in water, then mixing it with the YCl3 solution, adding a caustic soda solution dropwise and controlling the final pH value of the system to be 10-13, adding isopropanol, filtering, washing, and obtaining a yttrium-zirconium composite precipitate; wherein the weight ratio of the Zr(SO4)2, Y2O3, alkaline solution, and surfactant is 70:30:5:2;

[0051] (2) mixing the yttrium zirconium composite precipitate described in step (1) with nano-silicon dioxide, MgO and B2O3, smelting for 5 hours, pouring into a polyethylene glycol solution for water quenching, and filtering to obtain yttrium zirconium composite ceramic fragments; wherein the weight ratio of the yttrium zirconium composite precipitate, nano-silicon dioxide, MgO and B2O3 is 60:40:1:12, and the smelting is heated by intermittent heating, and the intermittent heating is stopped for 10 minutes after every 20 minutes of heating. The heating temperatures during the intermittent heating are 1800° C., 1200° C. and 600° C., respectively, and the process is repeated in sequence after each pause. The average particle size of the nano-silicon dioxide is 15 nm;

[0052] (3) Adding KAlSiO4, water glass, phosphate and Li2O to the yttrium-zirconium composite ceramic fragments of step (2), wet-milling at a rotation speed of 600 r / min for 10 h, drying and sieving to obtain yttrium-zirconium composite nano-ceramic powder; wherein the weight ratio of the yttrium-zirconium composite ceramic fragments, KAlSiO4, water glass, phosphate and Li2O is 60:40:10:3:1.

[0053] Example 4

[0054] Preparation of Yttrium-Zirconium Composite Nano-Ceramic Powder:

[0055] (1) dissolving ZrOCl2·8H2O in water, adding (NH4)2SO4, heating until solid precipitates, cooling, filtering, and obtaining Zr(SO4)2; dissolving Y2O3 in a hydrochloric acid solution to obtain a YCl3 solution; dissolving the Zr(SO4)2 in water, then mixing it with the YCl3 solution, dropping a urea solution and controlling the final pH value of the system to be 10-13, adding citric acid, filtering, and washing to obtain a yttrium-zirconium composite precipitate; wherein the weight ratio of the Zr(SO4)2, Y2O3, alkaline solution, and surfactant is 75:25:10:1;

[0056] (2) mixing the yttrium zirconium composite precipitate described in step (1) with nano-silicon dioxide, MgO and B2O3, smelting for 3 hours, pouring into a polyethylene glycol solution for water quenching, and filtering to obtain yttrium zirconium composite ceramic fragments; wherein the weight ratio of the yttrium zirconium composite precipitate, nano-silicon dioxide, MgO and B2O3 is 70:35:1.5:9, and the smelting is heated by intermittent heating, and the intermittent heating is stopped for 10 minutes after every 26 minutes of heating. The heating temperatures during the intermittent heating are 1800° C., 1200° C. and 600° C., respectively, and the cycle is repeated in sequence after each pause. The average particle size of the nano-silicon dioxide is 15 nm;

[0057] (3) Add KAlSiO4, water glass, phosphate, BaO and K2O to the yttrium-zirconium composite ceramic fragments of step (2), wet-mill at a rotation speed of 500 r / min for 20 h, dry and sieve to obtain yttrium-zirconium composite nano-ceramic powder; wherein the weight ratio of the yttrium-zirconium composite ceramic fragments, KAlSiO4, water glass, phosphate, BaO and K2O is 68:33:18:2:0.5:0.5.

[0058] Comparative Example 1

[0059] Preparation of Yttrium-Zirconium Composite Nano-Ceramic Powder:

[0060] (1) dissolving ZrOCl2·8H2O in water, adding (NH4)2SO4, heating until solid precipitates, cooling, filtering, and obtaining Zr(SO4)2; dissolving Y2O3 in a hydrochloric acid solution to obtain a YCl3 solution; dissolving the Zr(SO4)2 in water, then mixing it with the YCl3 solution, dropping an ammonia solution and controlling the final pH value of the system to be 10-13, adding glycerol, filtering, and washing to obtain a yttrium-zirconium composite precipitate; wherein the weight ratio of the Zr(SO4)2, Y2O3, alkaline solution, and surfactant is 78:20:10:1;

[0061] (2) mixing the yttrium zirconium composite precipitate of step (1) with nano-silicon dioxide, MgO and B2O3, smelting at a high temperature of 1800° C. for 4 hours, pouring into a polyethylene glycol solution for water quenching, and filtering to obtain yttrium zirconium composite ceramic fragments; wherein the weight ratio of the yttrium zirconium composite precipitate, nano-silicon dioxide, MgO and B2O3 is 70:35:1.5:10, and the average particle size of the nano-silicon dioxide is 15 nm;

[0062] (3) Adding KAlSiO4, water glass, phosphate and BaO to the yttrium-zirconium composite ceramic fragments of step (2), wet-milling at a rotation speed of 450 r / min for 25 h, drying and sieving to obtain yttrium-zirconium composite nano-ceramic powder; wherein the weight ratio of the yttrium-zirconium composite ceramic fragments, KAlSiO4, water glass, phosphate and BaO is 65:35:15:2:1.

[0063] Comparative Example 2

[0064] Preparation of Yttrium-Zirconium Composite Nano-Ceramic Powder:

[0065] (1) dissolving ZrOCl2·8H2O in water, adding (NH4)2SO4, heating until solid precipitates, cooling, filtering, and obtaining Zr(SO4)2; dissolving Y2O3 in a hydrochloric acid solution to obtain a YCl3 solution; dissolving the Zr(SO4)2 in water, then mixing it with the YCl3 solution, dropping an ammonia solution and controlling the final pH value of the system to be 10-13, adding glycerol, filtering, and washing to obtain a yttrium-zirconium composite precipitate; wherein the weight ratio of the Zr(SO4)2, Y2O3, alkaline solution, and surfactant is 78:20:10:1;

[0066] (2) mixing the yttrium zirconium composite precipitate described in step (1) with nano-silicon dioxide, MgO and B2O3, smelting for 4 hours, pouring into a polyethylene glycol solution for water quenching, and filtering to obtain yttrium zirconium composite ceramic fragments; wherein the weight ratio of the yttrium zirconium composite precipitate, nano-silicon dioxide, MgO and B2O3 is 70:35:1.5:10, and the smelting is heated by intermittent heating, and the intermittent heating is stopped for 10 minutes after every 25 minutes of heating. The heating temperatures during the intermittent heating are 1800° C., 1200° C. and 600° C., respectively, and the process is repeated in sequence after each pause. The average particle size of the nano-silicon dioxide is 15 nm;

[0067] (3) Adding water glass, phosphate and BaO to the yttrium zirconium composite ceramic fragments described in step (2), wet ball milling at a rotation speed of 450 r / min for 25 hours, drying and sieving to obtain yttrium zirconium composite nano-ceramic powder; wherein the weight ratio of the yttrium zirconium composite ceramic fragments, water glass, phosphate and BaO is 65:15:2:1.

[0068] Comparative Example 3

[0069] Preparation of Yttrium-Zirconium Composite Nano-Ceramic Powder:

[0070] (1) dissolving ZrOCl2·8H2O in water, adding (NH4)2SO4, heating until solid precipitates, cooling, filtering, and obtaining Zr(SO4)2; dissolving Y2O3 in a hydrochloric acid solution to obtain a YCl3 solution; dissolving the Zr(SO4)2 in water, then mixing it with the YCl3 solution, dropping an ammonia solution and controlling the final pH value of the system to be 10-13, adding glycerol, filtering, and washing to obtain a yttrium-zirconium composite precipitate; wherein the weight ratio of the Zr(SO4)2, Y2O3, alkaline solution, and surfactant is 78:20:10:1;

[0071] (2) mixing the yttrium zirconium composite precipitate described in step (1) with nano-silicon dioxide, MgO and B2O3, smelting for 4 hours, pouring into water for water quenching, and filtering to obtain yttrium zirconium composite ceramic fragments; wherein the weight ratio of the yttrium zirconium composite precipitate, nano-silicon dioxide, MgO and B2O3 is 70:35:1.5:10, and the smelting is heated by intermittent heating, and the intermittent heating is stopped for 10 minutes after every 25 minutes of heating. The heating temperatures during the intermittent heating are 1800° C., 1200° C. and 600° C., respectively, and the process is repeated in sequence after each pause. The average particle size of the nano-silicon dioxide is 15 nm;

[0072] (3) Adding KAlSiO4, water glass and BaO to the yttrium-zirconium composite ceramic fragments of step (2), wet-milling at a rotation speed of 450 r / min for 25 h, drying and sieving to obtain yttrium-zirconium composite nano-ceramic powder; wherein the weight ratio of the yttrium-zirconium composite ceramic fragments, KAlSiO4, water glass and BaO is 65:35:15:1.

[0073] Experimental example

[0074] The yttrium-zirconium composite nano-ceramic powders prepared in Examples 1-4 and Comparative Examples 1-3 were taken, and the average particle size and D97 particle size of the powders were measured;

[0075] The yttrium-zirconium composite nano-ceramic powders prepared in Examples 1-4 and Comparative Examples 1-3 were applied to the surface of stainless steel, respectively, and a layer of yttrium-zirconium composite nano-ceramic was sintered, and the compressive strength, density and stability were tested.

[0076] The compressive strength is tested according to the standard of GB / T 4740-1999.

[0077] Stability test: through 20℃-1200℃ cycle 10 times thermal shock test, calculate the powder removal rate per unit area.

[0078] The test data is shown in Table 1 below:

[0079] Table 1

[0080]

[0081] It can be seen from Table 1 that the yttrium zirconium composite nano-ceramic powder prepared in Examples 1-4 of the present application has a small particle size and a uniform particle size distribution. The prepared yttrium zirconium composite nano-ceramic powder has high compressive strength, good density, and is not easy to fall off during cyclic thermal shock.

[0082] The smelting in the preparation method of Comparative Example 1 adopts continuous high-temperature smelting, and the rest is the same as Example 1. The particle size of the yttrium zirconium composite nanoceramic powder prepared in Comparative Example 1 is slightly larger than that in Example 1, and the compressive strength of the prepared yttrium zirconium composite nanoceramic is significantly reduced, and the thermal stability and density are also deteriorated. This shows that the present application controls the heating time and interval during the smelting process through intermittent heating, so that the material has appropriate cooling time in the molten state, thereby avoiding quality instability caused by overheating. Through intermittent heating, it can be ensured that the material has sufficient time to diffuse and mix during the smelting process, making the composition more uniform and improving the overall quality of the composite ceramic.

[0083] The preparation raw materials of Comparative Example 2 do not contain KAlSiO4, and the rest are the same as Example 1. The particle size of the yttrium zirconium composite nanoceramic powder prepared in Comparative Example 1 is slightly larger than that in Example 1, and the compressive strength and density of the prepared yttrium zirconium composite nanoceramic are reduced, and the thermal stability is significantly deteriorated, indicating that the KAlSiO4 of the present application is a complex crystal composed of polyhedral coordination and has high thermal expansion. By combining with yttrium zirconium composite ceramics, the thermal expansion coefficient of yttrium zirconium composite ceramics can be improved, so that the thermal expansion coefficient of the prepared yttrium zirconium composite ceramics is close to that of stainless steel, which improves the bonding strength between the ceramic and stainless steel when subjected to thermal shock and improves the thermal stability.

[0084] The raw materials for the preparation of Comparative Example 3 do not contain phosphate and polyvinyl alcohol, and the rest are the same as those of Example 1. The particle size of the yttrium zirconium composite nanoceramic powder prepared in Comparative Example 1 is significantly larger than that in Example 1, and the compressive strength, density and thermal stability of the prepared yttrium zirconium composite nanoceramic are significantly worse, indicating that the addition of surfactant, polyethylene glycol solution and phosphate in the preparation method of the present application can improve the surface activity of yttrium zirconium nanopowder, reduce the agglomeration of powder, make the particle size distribution more uniform, and further improve the comprehensive performance of yttrium zirconium composite nanoceramic; the hydroxyl group and ether group in the polyethylene glycol molecule can form strong hydrogen bonds with the surface of the precipitated particles, and Moreover, its oxygen ether group is also easy to produce affinity with the surface of the precipitated particles. This interaction allows polyethylene glycol to be easily adsorbed on the surface of the particles to form a layer of polymer film, surrounding the precipitated particles, thereby effectively preventing the agglomeration of particles. Therefore, polyethylene glycol can form colloidal particles in aqueous solution and effectively prevent the aggregation of particles through the steric hindrance effect, thereby maintaining the stability of the dispersed system; phosphate esters can be adsorbed on the surface of powder particles, change their surface properties, reduce the attraction between particles, thereby preventing coagulation and agglomeration between particles, and can also maintain the dispersed state of the particles, thereby improving the stabilizing effect on yttrium-zirconium composite nano-ceramic powders.

[0085] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.

Claims

1. A method for preparing yttrium-zirconium composite nano-ceramic powder, characterized in that: The following steps are involved: (1) Dissolve ZrOCl2·8H2O in water, add (NH4)2SO4, heat until solid precipitates, cool and filter to obtain Zr(SO4)2; dissolve Y2O3 in hydrochloric acid solution to obtain YCl3 solution; dissolve the Zr(SO4)2 in water, then mix with the YCl3 solution, add alkaline solution dropwise and control the final pH of the system to 10-13, add surfactant, filter and wash to obtain yttrium-zirconium composite precipitate; (2) mixing the yttrium-zirconium composite precipitate described in step (1) with nano-silicon dioxide, MgO, and B2O3, smelting for 2-5 hours, pouring into a polyethylene glycol solution for water quenching, and filtering to obtain yttrium-zirconium composite ceramic fragments; (3) adding KAlSiO4, water glass and phosphate to the yttrium-zirconium composite ceramic fragments of step (2), grinding and drying to obtain yttrium-zirconium composite nano-ceramic powder; Wherein, the weight ratio of Zr(SO4)2, Y2O3, alkaline solution and surfactant in step (1) is (70-85):(10-30):(5-15):(0.5-2); The weight ratio of the yttrium-zirconium composite precipitate, nano-silicon dioxide, MgO and B2O3 in step (2) is (60-80):(30-40):(1-2):(8-12); In step (3), the weight ratio of the yttrium-zirconium composite ceramic fragments, KAlSiO4, water glass and phosphate is (60-70):(30-40):(10-20):(1-3); The smelting in step (2) is heated by intermittent heating; the intermittent heating is stopped for 10 minutes after every 20-30 minutes of heating; the heating temperatures during the intermittent heating are 1800°C, 1200°C, and 600°C, respectively, and the heating is cycled in sequence after each pause.

2. The method for preparing a yttrium-zirconium composite nano-ceramic powder according to claim 1, characterized in that: The surfactant in step (1) is selected from one of ethanol, isopropanol, glycerol and citric acid.

3. The method for preparing a yttrium-zirconium composite nano-ceramic powder according to claim 1, characterized in that: The alkaline solution in step (1) is selected from one of aqueous ammonia, ammonium carbonate, caustic soda and urea.

4. The method for preparing a yttrium-zirconium composite nano-ceramic powder according to claim 1, characterized in that: The grinding in step (3) is wet ball milling; the rotation speed of the wet ball milling is 300-600 r / min; and the time of the wet ball milling is 10-40 h.

5. The method for preparing a yttrium-zirconium composite nano-ceramic powder according to claim 1, characterized in that: The grinding in step (3) is followed by sieving to control the particle size distribution range of the product to be 50-200 nm.

6. The method for preparing a yttrium-zirconium composite nano-ceramic powder according to claim 1, characterized in that: Step (3) also includes adding at least one of BaO, K2O, Na2O, CaO, and Li2O before grinding.

7. Yttrium-zirconium composite nano-ceramic powder prepared by the method for preparing yttrium-zirconium composite nano-ceramic powder as claimed in any one of claims 1 to 6.

8. Application of the yttrium-zirconium composite nano-ceramic powder as claimed in claim 7 in the production of heat-resistant ceramics and aerospace.

9. Use of the yttrium-zirconium composite nano-ceramic powder as claimed in claim 7 in making a ceramic coating on the surface of stainless steel.

Citation Information

Patent Citations

  • Preparation of ZrO2-Al2TiO5-MgO composite nano powder

    CN101481246A

  • Yttrium zirconium composite nano-ceramic powder

    CN101550001A